Qualitative Study of Emergency Medicine Residents’ Perspectives of Trauma Leadership Development - Antionette McFarlane; Sarah M. Brolliar; Elizabeth D. Rosenman; Joshua A. Strauss; James A. Grand; Rosemarie Fernandez (Western Journal of Emergency Medicine, 2023)
Background: Trauma team leadership is a core skill for the practice of emergency medicine (EM). In this study our goal was to explore EM residents’ perception of their trauma leadership skill development through formal and informal processes and to understand factors that may impact the development and implementation of trauma leadership skills. Methods: Using qualitative semi-structured interviews, we explored the leadership experiences of 10 EM residents ranging from second to fourth postgraduate year. Interviews were conducted between July 26–October 31, 2019 and were audio-recorded, transcribed, and de-identified. We analyzed data using qualitative content analysis. Results: Residents discussed three main themes: 1) sources of leadership development; 2) challenges with simultaneously assuming a dual leader-learner role; and 3) contextual factors that impact their ability to assume the leadership role, including the professional hierarchy in the clinical environment, limitations in the physical environment, and gender bias. Conclusion: This study describes the complex factors and experiences that contribute to the development and implementation of trauma team leadership skills in EM residents. This includes three primary sources of leadership development, the dual role of leader and learner, and various contextual factors. Research is needed to understand how these factors and experiences can be leveraged or mitigated to improve resident leadership training outcomes.